Acute Effects of Different Intensities of Flywheel Half Squat Based on Velocity on Vertical Jump Performance in High-Level Athletes - Xixuan Wang; Haiting Zhai; Hongwen Wei (Applied Sciences)
Coaches manipulate training variables to optimize and improve them, with intensity being crucial. Velocity-based training, measuring intensity by the movement speed, is advantageous over traditional methods. Flywheel training, offering concentric and eccentric loads, allows for supramaximal loading during the eccentric phase, enhancing muscle hypertrophy and performance and reducing injury risk. This study examines the specific effects of flywheel training on post-activation potentiation (PAP). Forty-one high-level male athletes performed flywheel half squats at fast (0.95–1.05 m/s), medium (0.65–0.75 m/s), and slow (0.35–0.45 m/s) speeds. Their drop jump performance was assessed at 30 s and 4, 8, and 12 min post-induction. Lower-limb kinematic data and ground reaction forces were recorded using infrared motion capture and force plates. Measures included peak collision force, peak extension force, knee joint extension moment, knee joint power, average power output, and vertical jump height. High-speed intensity significantly increased peak impact force, peak vertical ground reaction force, knee joint eccentric power, concentric power, and extension torque at 4, 8, and 12 min post-induction (p < 0.05). Fast- (0.95–1.05 m/s) and medium-speed (0.65–0.75 m/s) flywheel squats acutely improved lower-limb performance, especially vertical jump height, within 4–12 min post-stimulation. Fast-speed loading showed greater benefits for reactive strength and power output, while a medium speed also yielded meaningful gains. These findings support using movement velocity to guide flywheel training intensity.